Women Workforce in the Korean Context - Lee, Yeonu (International Review of Management and Marketing, 2017)
The social participation of women workforce in the labour market is now more prevalent than ever, however the promotion opportunities for women employees are limited compared to men in the Korean context. The article explores the impact of the Confucian tradition on women employees and as a result the traditional value causes difficulties for women employees to gain promotion than men in organisations. Also this article discusses why Korean women need to overcome the ‘glass ceiling' more compared to other countries. In addition, this article examines the factors which impact women employees to curtail work efficiency in service companies. Lastly, this article brings different actors of HR managers, trade union representatives and employees together to fully understand the gender relations at workplaces. Keywords: Women Workforce, Confucianism, Glass ceiling JEL Classifications: J82, L83